The Influence of Brand Characteristic on Customer Brand Relationship Through Consumer Engagement as Mediator - Yasmine Putri Gustano; Nurafni Rubiyanti (Jurnal Informatika Ekonomi Bisnis, 2023)
KRB.ID a knitwear business located in the Binong Jati knitting industry area, Indonesia. KRB.ID was established at the beginning of the COVID-19 pandemic and witnessed significant growth during this challenging period. Leveraging the expanding popularity of TikTok during the pandemic, KRB.ID used video content to raise brand awareness among TikTok users. Many of their videos gained visibility on TikTok's "For You Page" (FYP), leading to increased recognition and a growing TikTok following. Understanding the importance of engagement on social media platforms, KRB.ID actively interacted with their customers by responding to comments through video replies and various other means. One notable video featured four women wearing KRB.ID's skirt products, showcasing their versatility across different body sizes (ranging from 47kg to 80kg), positioning the brand as inclusive and big-size friendly. The video garnered 3,600,000 views, 61,300 likes, and received 729 comments from TikTok users. Currently, KRB.ID's TikTok account boasts 58,800 followers. However, in mid-2022, a decline in engagement was observed on KRB.ID's TikTok account, prompting the researcher to investigate this phenomenon using theories of brand characteristics, customer brand relationships, and consumer engagement.